2009
DOI: 10.1111/j.1752-699x.2008.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Collagen V and vascular injury promote lung architectural changes in systemic sclerosis

Abstract: We conclude that the endothelial apoptosis and vascular collagen V interaction reinforce the vascular pathway in the SSc pathogenesis. Further studies are needed to determine whether this relationship is causal or consequential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 23 publications
1
23
0
6
Order By: Relevance
“…An imbalance in the equilibrium of iNOS and other isoform (nNOS and eNOS) synthesis and the resulting increased production of NO have been reported to be associated with serious cell damage (28). In the present study, the grades at which greatest endothelial damage occurred were the same as those in which morphological studies from this laboratory have shown evidence of endothelial injury and death (18). In other situations, such as vascular changes associated with endotoxic shock (29), and ischemia-reperfusion injuries (30), endothelial iNOS expression has been associated with endothelial damage mediated by free radicals.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…An imbalance in the equilibrium of iNOS and other isoform (nNOS and eNOS) synthesis and the resulting increased production of NO have been reported to be associated with serious cell damage (28). In the present study, the grades at which greatest endothelial damage occurred were the same as those in which morphological studies from this laboratory have shown evidence of endothelial injury and death (18). In other situations, such as vascular changes associated with endotoxic shock (29), and ischemia-reperfusion injuries (30), endothelial iNOS expression has been associated with endothelial damage mediated by free radicals.…”
Section: Discussionsupporting
confidence: 53%
“…Excessive levels of NO react with superoxides to form peroxynitrite and highly reactive hydroxyl radicals, which in turn result in cell injury and apoptosis (17). As the histopathological changes in the lungs of patients with SSc are consistent with alveolar and vessel cell damage (18-20), we presume that this interaction can be characterized by analyzing the expression of proteins regulating NO synthesis. To validate the importance of alveolar-vascular interactions and to explore the quantitative relationship between these factors and the outcome, as well as the relationship between these factors and other clinical data and pulmonary function tests, we studied these markers in 23 SSc-NSIP cases.…”
Section: Introductionmentioning
confidence: 96%
“…Endothelial apoptosis in vascular pathology of SS . COLV is proapoptotic; apoptosis of the endothelium of pulmonary vessels is a unique histological abnormality associated with SS (Parra et al, ). In the lung biopsies of SS patients, the endothelial apoptosis is accompanied by vascular basement membrane disruption and COLV overexpression in the vessel walls, all of which likely contribute to the vascular damage in the pathogenesis of SS.…”
Section: Disease and Fibrosismentioning
confidence: 99%
“…Isto sugeriu o uso da droga como um modelo animal de diabetes e como um tratamento médico para câncer das células beta. Atualmente essa droga tem ampla utilização na indução de diabetes experimental [63][64][65][66]. Em síntese, o comprometimento articular no DM, até o presente momento, foi pouco estudado.…”
unclassified